Tuberculosis in children and adolescents of various age groups in Saratov Region - E. N. Аleksandrova; T. I. Morozova; N. P. Doktorova (Туберкулез и болезни лёгких)
Given the stabilization of tuberculosis epidemiological situation in Saratov Region, there is reduction of tuberculosis incidence both in children and adolescents, which is due to the performed tuberculosis control activities aimed at early detection and prevention of tuberculosis. Cases of 150 children and 125 adolescents treated at the Saratov RTBD from 2009 to 2013 were analyzed. It was found out that preventive detection of tuberculosis was equally efficient in children and adolescents (p = 0.3024). Wide introduction of computer tomography and Diaskintest into practice increased the number of persons followed up as Group 0 twice in 2013 compared to 2009 (p = 0.0038) and it caused the increase in the frequency of tuberculous intoxication (p = 0.0422) and focal tuberculosis in the structure of clinical forms of tuberculosis in children. Exposure to tuberculosis was found in 48.7% of followed-up cases among children and in 25.6% among adolescents. The father was the most common source of infection. The lack of quality immune prevention in children during first 2 years of life promoted the development of local tuberculosis.